2019
DOI: 10.1590/1983-80422019273322
|View full text |Cite
|
Sign up to set email alerts
|

Diálise e direito de morrer

Abstract: Resumo A doença renal crônica atinge níveis epidêmicos em praticamente todos os países. No Brasil, mais de 30 mil pessoas por ano precisam de tratamento dialítico, sendo mais comum a hemodiálise. Se, por um lado, a falta de vagas para diálise é o principal problema, por outro, têm crescido os casos de recusa e abandono do tratamento. Este artigo trata justamente dessa questão, a partir de temas como sentidos da vida e da morte, autonomia e terminalidade. Foram identificadas algumas estratégias que pode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Besides, some reported that they know the check-up is necessary but do not know how to talk to their parents about this type of care. Rodrigues and Fernandes (2019) [9] mentioned that the young may behave differently when they are accompanied by parents to see a physician. Parents also play a key role in medical assistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, some reported that they know the check-up is necessary but do not know how to talk to their parents about this type of care. Rodrigues and Fernandes (2019) [9] mentioned that the young may behave differently when they are accompanied by parents to see a physician. Parents also play a key role in medical assistance.…”
Section: Resultsmentioning
confidence: 99%
“…Parents also play a key role in medical assistance. There are situations in which physicians must consider adolescents' safety and balance the bioethical pillars of Medicine to justify confidentiality breach [9].…”
Section: Resultsmentioning
confidence: 99%